L-theanine promotes angiogenesis in limb ischemic mice by modulating NRP1/VEGFR2 signaling - Jingyi Wang; Yinghui Xu; Yating Ruan; Xinyang Hu (Biomolecules & Biomedicine)
Peripheral artery disease (PAD), primarily caused by atherosclerosis, leads to the narrowing or blockage of arteries that supply blood to the limbs. This study explores the pro-angiogenic effects of L-theanine and its underlying mechanisms in a mouse model of hindlimb ischemia (HLI). To evaluate L-theanine's pro-angiogenic effects, human umbilical vein endothelial cells (HUVECs) were subjected to tube formation, migration, sprouting, and proliferation assays. In vivo, C57BL/6 mice with induced HLI were treated with L-theanine. Blood flow recovery was measured via Doppler ultrasound, and vascular density was analyzed using immunofluorescence staining. RNA sequencing identified neuropilin-1 (NRP1) as a key regulator, and the expression levels of NRP1 and VEGFR2 were examined through qPCR and Western blotting. L-theanine significantly enhanced angiogenesis in HUVECs, as demonstrated by improved tube formation, migration, sprouting, and proliferation. In mice, L-theanine treatment resulted in increased vessel density and improved blood flow recovery. Furthermore, L-theanine was found to activate the NRP1/VEGFR2 signaling pathway in both HUVECs and the HLI mouse model. These findings indicate that L-theanine can promote angiogenesis and activate key pathways involved in vascular repair, suggesting its potential as a therapeutic agent for treating vascular defects associated with PAD.